Formulation and Optimization of Dispersible Tablets for NSAIDs: Enhancing Drug Delivery and Efficacy - Monali Shewale (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: This paper explores strategies for formulating and optimizing dispersible tablets containing Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). Emphasis is placed on enhancing drug delivery through rapid disintegration, stability considerations, optimization techniques, and evaluation methods to ensure efficacy. Methodology: The formulation of dispersible NSAID tablets involves careful selection of excipients such as disintegrants, binders, and lubricants to achieve rapid disintegration and adequate stability. Optimization strategies, including Design of Experiments (DoE) for parameter tuning and compression force adjustments, are employed to enhance tablet characteristics like hardness and disintegration time. Results: Evaluation of the optimized dispersible tablet formulation includes in vitro studies for disintegration and dissolution rates, drug release kinetics analysis, and physicochemical characterization (e.g., SEM, XRD). These studies demonstrate the effectiveness of the formulation in achieving rapid drug delivery and maintaining stability under storage conditions. Conclusion: Formulation and optimization of dispersible tablets for NSAIDs represent a promising approach to improve drug delivery and efficacy. Future research should focus on refining these formulations to enhance bioavailability, minimize side effects, and tailor treatment options to individual patient needs, thereby advancing personalized medicine in pain management and inflammatory conditions.